2021
DOI: 10.1111/and.14282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumin, and nano‐curcumin on sperm function in varicocele rat model

Abstract: One of the main and acceptable causes of infertility in men is 'varicocele' due to the abnormal enlargement and dilation of the testicular veins (especially the left one), the pathological consequences of which are testicular damage and reduced sperm quality (Jensen et al., 2017). According to the literature background, several mechanisms could account for these pathological consequences including hypoxia, increased testicular temperature, changes in testicular blood flow and venous pressure, stasis, inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In fact, there are some debates about the biological activity of curcumin because it is an unstable, reactive, nonbioavailable compound, which is also considered a PAINS medication [ 260 ]. Some studies have found no significant difference between curcumin and placebo [ 261 ], but some pharmacological activities of curcumin have been validated in animal experiments and clinical trials in recent years [ 262 , 263 , 264 , 265 ]. Many factors affect the activity of curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, there are some debates about the biological activity of curcumin because it is an unstable, reactive, nonbioavailable compound, which is also considered a PAINS medication [ 260 ]. Some studies have found no significant difference between curcumin and placebo [ 261 ], but some pharmacological activities of curcumin have been validated in animal experiments and clinical trials in recent years [ 262 , 263 , 264 , 265 ]. Many factors affect the activity of curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Noorafshan et al, showed that CUR ameliorated the round or long spermatid, testis weight, volume, and germinal epithelium volume in metronidazole-treated rats [ 31 ]. Sadraei et al, reported that CUR-n 4 mg and 8 mg significantly increased sperm number and sperm motility and decreased sperm with abnormal morphology [ 15 ]. In consistent with our study, Abdelnour et al, demonstrated that treatment with nano-CUR at a concentration of 1.5 mg/ml reduced percentages of dead sperm, abnormalities, early apoptotic, apoptotic, and necrotic sperm cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Ahmed-Farid et al, exhibited that CUR nano-emulsion (2.5 and 5 mg/kg) enhanced serum testosterone levels, sperm motility, testicular GSH, CAT, SOD, testicular cell energy (ATP, ADP, and AMP), essential and non-essential amino acids in seminal plasma, and declined testicular MDA, NOx, GSSG and 8-OHDG [ 14 ]. Similarly, Sadraei et al, revealed that antioxidant therapy with nano CUR significantly reduced serum lipid peroxidation and ROS [ 15 ]. In a randomized clinical trial conducted by Alizadeh et al, CUR-n supplementation significantly improved total sperm count, sperm concentration, and motility, plasma levels of TAC, MDA, C-reactive protein, and tumor necrosis factor in comparison to the placebo [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from zinc and cerium, other nanoantioxidant formulations, such as curcumin, selenium, and vitamin E, were reported to reduce OS and improve sperm function or parameters [ 147 ]. Varicocele-induced rats orally treated with nano-curcumin showed improvement in testicular function with decreased ROS and LPO levels and reduced sperm DNA fragmentation [ 148 ]. The injection of iron oxide NPs coated with curcumin in a group of mice (exposed to testicular hyperthermia) resulted in higher testosterone levels, lower apoptotic spermatozoa, and increased germ cell proliferation compared to other groups [ 149 ].…”
Section: Therapeutic Modalities To Reduce Seminal Osmentioning
confidence: 99%